2010
DOI: 10.1186/1752-0509-4-37
|View full text |Cite
|
Sign up to set email alerts
|

An integrated machine learning approach for predicting DosR-regulated genes in Mycobacterium tuberculosis

Abstract: BackgroundDosR is an important regulator of the response to stress such as limited oxygen availability in Mycobacterium tuberculosis. Time course gene expression data enable us to dissect this response on the gene regulatory level. The mRNA expression profile of a regulator, however, is not necessarily a direct reflection of its activity. Knowing the transcription factor activity (TFA) can be exploited to predict novel target genes regulated by the same transcription factor. Various approaches have been propos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…As a first example of complex SSMs, Zhang et al . used gaussian processes dynamical models with nonlinear dynamics to infer the profile of a single transcription factor (the tumor suppressor p53) and explained the activity of a large collection of genes using that transcription factor only (without any other transcription factor-gene interaction) [ 39 ]. Another example is the linear dynamical system, which Beal et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a first example of complex SSMs, Zhang et al . used gaussian processes dynamical models with nonlinear dynamics to infer the profile of a single transcription factor (the tumor suppressor p53) and explained the activity of a large collection of genes using that transcription factor only (without any other transcription factor-gene interaction) [ 39 ]. Another example is the linear dynamical system, which Beal et al .…”
Section: Resultsmentioning
confidence: 99%
“…Because our noise reduction state-space modeling algorithm is efficient, simple and tractable, as explained in the Materials and methods section, it can handle larger numbers of genes (we focused on 76 genes) than other SSM approaches, given enough genes [ 37 - 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, expression levels of these TFs will not always be sufficient to reflect their activity since the activity of a transcription factor (TFA) is controlled by various post-translational modifications as well as co-activator and co-repressor activities. Previous works by us and others have shown that TFA can be best inferred from the transcript levels of its direct target genes, rather than its mRNA level using Network Component Analysis (NCA) [15] , [16] , [17] . NCA is a model-based decomposition method to deduce transcription factor activity (TFA) and regulation control strength (CS) of TFs from target gene expression and information of TF - gene interactions.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, DosR recognizes a fairly conserved 18/20-bp palindromic sequence that is present with some variation upstream of the transcriptional units for these genes (Table 3) (4,25,26,42,55,116,125,162). Similar sequences are also found upstream of other genes outside this regulon, although their regulation by DosR remains unclear (116,185). Promoter regions from DosR regulon genes often contain two or more sets of recognition sequences, and cooperative binding by DosR to these sites is necessary for their full induction (24)(25)(26).…”
Section: Devr-devs-rv2027c or Dosr-doss-dostmentioning
confidence: 73%